A Single Center Study on Demographic Profile of Patients Undergoing Coronary Angiogram - Akanda, Md Abdul Kader; Reza, Abeeda Tasnim; Akanda, Md Muhtasim (Bangladesh Heart Journal, 2024)
Background: The aim of this study was to observe demographic profile of patients undergoing coronary angiogram (CAG) in a single center. Method: The data was derived from a prospective observational study to observe the demographic profile of patients undergoing coronary angiogram for 2 years. A total of 176 patients undergoing coronary angiogram were randomly selected and enrolled from 2018 to 2019 in an urban cardiac hospital of Bangladesh. The study population were divided into two groups with group 1 consisting of patients with normal coronaries (n=45) and group 2 consisting of patients having coronary artery disease (CAD) (n=131). Age, sex, risk factors & investigation findings were noted and compared between two groups. Results: Most of the patients (120) belonged between 41-60 years age group. This age group had the maximum patients with abnormal CAG & normal CAG. Most of the study populations were male (73.9%). Among the female study population (26.1%), most of them had normal coronaries rather than CAD (52% vs 48%). Most of the study population with abnormal CAGs had normal body mass index (BMI). Those having CAD had higher percentage of risk factors in comparison to those having normal coronaries. Among all the risk factors, there were significant difference in respect of diabetes & smoking between the two groups (p=0.007 & <0.001, respectively). Most of the CAD patients had presence of 2 or more risk factors. Dx: Significant difference was noted among the 2 group in respect of random blood sugar & serum creatinine level. Echo: , TVD, DVD, SVD, LM, Right dominant Conclusions: Higher percentage of patients undergoing coronary angiogram had abnormal coronaries. (Bangladesh Heart Journal 2024; 39(2):102-107